A review on allotropes of carbon and natural filler-reinforced thermomechanical properties of upgraded epoxy hybrid composite - Gouda Krushna (De Gruyter, 2021)
The scarcity of nonrenewable resource motivated inclination towards the environmental-friendly novel materials and development of waste natural filler-based hybrid composite is encouraged to fulfill the material demand. Epoxy resins-based composites are high-performing thermosetting polymers and have outstanding blending properties, good machinability, and low cost. Due to these advantages, thermoset plastic is largely used in a broad range of engineering applications; however, thermomechanical properties of neat epoxy are low. Thus, to enhance the thermomechanical properties of epoxy, it is interfaced materials such as graphite, graphene nanoplatelet, boron, carbon fiber, aluminium, silver, etc. Among various substances, graphene has been deliberated as an acceptable novel filler because of its exceptional properties. In addition to inorganic filler inclusion, natural filler/fiber like hemp, sisal, flax, bamboo, jute, etc. can be utilized in a higher percentage as biodegradable material. The present article assisted to improve thermomechanical properties of neat epoxy. This work identifies and addresses (i) processes used for graphene modification; (ii) treatment utilized for enhancing the binding properties of natural filler; (iii) various natural filler extraction process employed; (iv) neat epoxy modification; and (v) influence of different dimensions of fillers.